2001
DOI: 10.1001/archpsyc.58.5.494
|View full text |Cite
|
Sign up to set email alerts
|

Supportive-Expressive Group Therapy and Distress in Patients With Metastatic Breast Cancer

Abstract: Supportive-expressive therapy, with its emphasis on providing support and helping patients face and deal with their disease-related stress, can help reduce distress in patients with metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
309
1
16

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 455 publications
(341 citation statements)
references
References 54 publications
13
309
1
16
Order By: Relevance
“…The 21-item scale yields a total score and 5 subscale scores: New Possibilities, Relating to Others, Personal Strength, Spiritual Change, and Appreciation of Life. Items are rated on a 6-point Likert scale, ranging from "I did not experience this change as a result of my crisis" (0) to "I experienced this change to a very great degree as a result of my crisis" (5). "My priorities about what is important in life."…”
Section: 90mentioning
confidence: 99%
See 1 more Smart Citation
“…The 21-item scale yields a total score and 5 subscale scores: New Possibilities, Relating to Others, Personal Strength, Spiritual Change, and Appreciation of Life. Items are rated on a 6-point Likert scale, ranging from "I did not experience this change as a result of my crisis" (0) to "I experienced this change to a very great degree as a result of my crisis" (5). "My priorities about what is important in life."…”
Section: 90mentioning
confidence: 99%
“…However, previous clinical trials of face-to-face support groups [5][6][7][8] for women with breast carcinoma demonstrate significant evidence of 1) an improvement in quality of life, 2) a reduction of psychologic symptoms, 3) an improvement in coping responses, and 4) a reduction in pain. Recent reports also indicate that positive effects from group interventions can be found in women from different cultures.…”
mentioning
confidence: 99%
“…1,4 -7 These trials are summarized in Table 1. Four 1,13-15 of the five trials have reported survival outcomes; and one additional trial, 16 which represents the attempt by Spiegel et al to replicate their previously reported survival benefit, has not yet produced a report of survival effects.…”
Section: The Current Evidencementioning
confidence: 99%
“…It also has been argued that women in the control arm of the study did not live as long as women with metastatic breast cancer in the community, leading to concerns that the control group in the study by Spiegel et al was not an appropriate comparison group (although the intervention and control arms were formed by randomization). 19 In evaluating this criticism, it should be pointed out that the main purpose of randomization is to avoid bias in treatment allocation, not to ensure that the control group is 16 and the other, 15 which was conducted by our group, involved training of group leaders by Spiegel to ensure that the intervention was replicated accurately. Two other groups 13,14 used shorter interventions (35 weeks, 5 mos) that included cognitive-behavioral group therapy and, in one study, 13 elements of supportive-expressive therapy as well as coping skills training.…”
Section: Effect Of Group Support On Survival In Metastatic Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation